Comparison between 8‐ and 32‐channel phased‐array receive coils for in vivo hyperpolarized 13C imaging of the human brain. Issue 2 (29th March 2019) - Autry, Adam W.; Gordon, Jeremy W.; Carvajal, Lucas; Mareyam, Azma; Chen, Hsin‐Yu; Park, Ilwoo; Mammoli, Daniele; Vareth, Maryam; Chang, Susan M.; Wald, Lawrence L.; Xu, Duan; Vigneron, Daniel B.; et al.
Abstract : Purpose: To compare the performance of an 8‐channel surface coil/clamshell transmitter and 32‐channel head array coil/birdcage transmitter for hyperpolarized 13 C brain metabolic imaging. Methods: To determine the field homogeneity of the radiofrequency transmitters, B1 + mapping was performed on an ethylene glycol head phantom and evaluated by means of the double angle method. Using a 3D echo‐planar imaging sequence, coil sensitivity and noise‐only phantom data were acquired with the 8‐ and 32‐channel receiver arrays, and compared against data from the birdcage in transceiver mode. Multislice frequency‐specific 13 C dynamic echo‐planar imaging was performed on a patient with a brain tumor for each hardware configuration following injection of hyperpolarized [1‐ 13 C]pyruvate. Signal‐to‐noise ratio (SNR) was evaluated from pre‐whitened phantom and temporally summed patient data after coil combination based on optimal weights. Results: The birdcage transmitter produced more uniform B1 + compared with the clamshell: 0.07 versus 0.12 (fractional error). Phantom experiments conducted with matched lateral housing separation demonstrated 8‐ versus 32‐channel mean transceiver‐normalized SNR performance: 0.91 versus 0.97 at the head center; 6.67 versus 2.08 on the sides; 0.66 versus 2.73 at the anterior; and 0.67 versus 3.17 on the posterior aspect. While the 8‐channel receiver array showed SNR benefits along lateral aspects, the 32‐channel array exhibited greater coverage and a more uniform coil‐combined profile. Temporally summed, parameter‐normalized patient data showed SNRmean, slice ratios (8‐channel/32‐channel) ranging 0.5‐2.00 from apical to central brain. White matter lactate‐to‐pyruvate ratios were conserved across hardware: 0.45 ± 0.12 (8‐channel) versus 0.43 ± 0.14 (32‐channel). Conclusion: The 8‐ and 32‐channel hardware configurations each have advantages in particular brain anatomy.